Revisiting the term neuroprotection in chronic and degenerative diseases - Marco Orsini; Osvaldo J.M. Nascimento; Andre P.C. Matta; Carlos Henrique Melo Reis; Olivia Gameiro de Souza; Victor Hugo Bastos; Rayele Moreira; Pedro Ribeiro; Stenio Fiorelli; Pietro Novellino; Bruno Pessoa; Mariana Cunha; et al. (MDPI AG, 2016)
Thanks to the development of several new researches, the lifetime presented a significant increase, even so, we still have many obstacles to overcome − among them, manage and get responses regarding neurodegenerative diseases. Where we are in the understanding of neuroprotection? Do we really have protective therapies for diseases considered degeneratives such as amyotrophic lateral sclerosis and its variants, Parkinson's disease, Alzheimer's disease and many others? Neuroprotection is defined by many researches as interactions and interventions that can slow down or even inhibit the progression of neuronal degeneration process. We make some considerations on this neuroprotective effect.